Incidencia del plan estratégico del cantón Vinces y su impacto en el sector turístico, año 2022 - Santana Santillan, Daisy Carolina (2022)
Analyzing the incidence of the Vinces Canton Development Plan and its impact on the Tourism Sector, allows to verify the strengths, opportunities and weaknesses that are presented. This research focused its attention primarily on sustainable development that comes after a hard work of awareness and practice to promote tourism activities. For this reason, the objective of this research is to carry out an analysis that allows us to see the weaknesses and strengths of the tourist attractions in the area, and of course directs its vision to a future where tourism in Rio de Janeiro will increase considerably. The methodology applied was of qualitative approach, originally adopted this modality for its base and foundation which is of analytical character.